Digital Transformation in Small and Medium Enterprises (SMES): Challenges and Opportunities in Indonesia - Tegar Ainurrokhim; Kiskendra Citra Hati; Naufal Daffa Adibta (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
The rapid pace of digital transformation presents both challenges and opportunities for Small and Medium Enterprises (SMEs) in Indonesia. This paper explores how SMEs are adapting to digital change, highlighting the main barriers and enabling factors affecting their growth. Through qualitative interviews with SME owners across Indonesia, the study uncovers key themes around technological adoption, financial investment, and skill gaps. The findings suggest that while digital adoption can enhance competitiveness and efficiency, SMEs require support in terms of digital literacy and funding access. Policy recommendations include enhancing government support, providing digital training programs, and offering incentives for digital investments.